PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN KEPERCAYAAN PASIEN RAWAT INAP RUMAH SAKIT UMUM DAERAH SELASIH KAB. PELALAWAN - Adhitio Pratama; Alvi Furmawati; Bambang Rianto Rustam (Jurnal Economica, 2019)
As a refferal hospital to anticipate the patient need of Health Service in Pelalawan District’s, and the needed to compete the private hospital, Selasih District Hospital has a mandatory work to increase the service quality index and patient trust. The finding of this research show that the increase of patient in condition of low quality of service given by the Selasih Hospital, show that there is a contradictory to Customer Behavioural Theory, which state that a loyal consumer exist because of the high quality of service and the more costumer show their trust. The research’s design is a quantitative research approach, and using questionnaire as a data collection for 83 sample by 483 population, that is Selasih Hospital’s VIP Patient. This research data collection using a documentation technique for secunder data, which is come from Research Object. Data was being analyzed with Partial Least Square Approach, where Customer Satisfaction as Intervening Variable. The result of this research show that Service Quality has positive and significance effect to both Customer Satisfaction and Customer’s Trust. This result reveal that Customer Satisfaction has mediating effect for Service Quality to Customer’s Trust. This research suggestion is “a needed for medical officer in Selasih Hospital to increased their responsiveness and emphaty on customer complaint and help, and practicing the good governance and a cost transparentcy, so that the customer can be satisfied and get more trust.